2021
DOI: 10.3390/ijerph18115973
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and Pharmaceutical Care: Interprofessional, Evidence-Based Working to Improve Patient Care and Outcomes

Abstract: Pharmaceutical care necessitates significant efforts from patients, informal caregivers, the interprofessional team of health care professionals and health care system administrators. Collaboration, mutual respect and agreement amongst all stakeholders regarding responsibilities throughout the complex process of pharmaceutical care is needed before patients can take full advantage of modern medicine. Based on the literature and policy documents, in this position paper, we reflect on opportunities for integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Participants felt that therapeutic collaboration between caring professionals, including interprofessional and multi-disciplinary teams needs to be strengthened. Safety during transition of patients between types of care including discharge planning and follow-up were areas of special concern which they felt demanded structured interaction and cooperation between the sectors of the healthcare team (De Baetselier et al, 2022;Dilles et al, 2021;Mardani et al, 2020;Setter et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants felt that therapeutic collaboration between caring professionals, including interprofessional and multi-disciplinary teams needs to be strengthened. Safety during transition of patients between types of care including discharge planning and follow-up were areas of special concern which they felt demanded structured interaction and cooperation between the sectors of the healthcare team (De Baetselier et al, 2022;Dilles et al, 2021;Mardani et al, 2020;Setter et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Profession caring aspects of PC enumerated in that resolution included holistic assessment of patient status and characteristics, identification of medication-related problems, formulation of a client care plan, implementation and monitoring of care, and follow-up on the patient's status (De Baetselier et al, 2020). Dilles et al (2021) enumerated the scope of nurse PC as the monitoring of client responses to and compliance with medication, prescription and administration of medicines, and provision of patient education and information during clinical practice. The mandated ability to perform these functions varies across Council of Europe member states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medication safety programmes have been introduced in many hospitals to minimize the likelihood of harm associated with the use of medication, and maximize the benefits for patients [ 28 ]. Adopting facets like medication safety policy, multidisciplinary team policy, double checking policy as well as adopting electronic prescribing system are common safety practices activated in hospitals [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' contributions to medical care and pharmaceutical care will reduce the barrier of nurses' collaboration with other professions. A systematic review had reported that, in more than 30% (15 out of 50 studies) of the included studies, nurses were heavily involved in interventions for improving patients' care, especially patients' adherence towards medication [29]. Pharmacists were reported to have higher barriers in collaboration than nurses because of limited doctor and nurse knowledge about the pharmacists' competencies.…”
Section: Profession Influences Cpat Perceptionmentioning
confidence: 99%